Energy analysis for production of powdered and pelletised organic fertilizer in Nigeria (2006)
Energy study was conducted in an organic fertilizer plant in Ibadan, Nigeria, to determine the energy requirement for production of both powdered and pelletised organic fertilizer. The energy consumption patterns of the unit operations were evaluated for production of 9,000 kg of the finished products. The analysis revealed that eight and nine defined unit operations were required for the production of powder and pellets, respectively. The electrical and manual energy required for the production of powdered fertilizer were 94.45 and 5.55% of the total energy, respectively, with corresponding 93.9 and 5.07% for the production of pelletised fertilizer. The respective average energy intensities were estimated to be 0.28 and 0.35 MJ/kg for powder and pellets. The most energy intensive operation was identified as the pulverizing unit with energy intensity of 0.09 MJ/kg, accounting for respective proportions of 33.4 and 27.0% of the total energy for production of powder and pellets. Optimisation of the pulverizing process is suggested to make the system energy efficient.